The Construction of National Values foor Indonesian Citizens at the Border in the Framework of the Universal War Strategy - Maisondra, Maisondra; Midhio, I Wayan; Perwata, Anak Agung Banyu (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia shares direct land borders with three countries, namely: Malaysia, Timor Leste, Papua New Guinea. These three countries influence all regional political, economic and security dynamics with Indonesia. This research, using a descriptive qualitative method, utilized Human Security theory, National Security Policy of the Republic of Indonesia, the Concept of Universal War Strategy and the Concept of National Defense, as well as using the opinions of a number of experts in its analysis. The results show that a number of conditions in Indonesian society in border areas can influence feelings of nationalism and patriotism. Based on the results of the research conducted, it is recommended that stakeholders prioritize various National Values ​​Strengthening programs for border area communities.